Does antioxidant potential of traditional rice varieties vary with processing? - Thennakoon, T.P.A.U.; Ekanayake, S. (Faculty of Graduate Studies , University of Sri Jayewardenepura, 2021)
Antioxidants protect cells and tissues from free radical damage and therefore, are important in the prevention and management of a variety of chronic diseases. Bran of pigmented rice are potent sources of naturally occurring antioxidants. Rice being the staple diet of Sri Lankans and traditional rice gaining more attention at present, investigating the effect of processing and cooking on total phenol content and antioxidant potentials of selected traditional rice varieties were the aims of this study. Differently processed (raw undermilled, raw polished [4%] and parboiled undermilled) six rice varieties, namely, Godaheenati, Batapola el, Dik wee, Dahanala, Unakola samba and, Hangimuththan were used in the study. The antioxidant properties of rice flour extracted with phosphate buffer solution (PBS) were determined by 2,2’-azino-bis (3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) radical scavenging activity, 1,1-diphenyl-2-picrylhydrazine (DPPH) radical scavenging activity and, ferric reducing antioxidant power (FRAP)assays. Moreover, the total polyphenolic content (TPC) of differently processed rice was analysed. Mean TPC of both uncooked and cooked, raw polished rice was the least (4.9-6.1 mg GAE/g) followed by parboiled (4.9-6.1 mg GAE/g). The highest TPC was in raw (5.3-6.7 mg GAE/g) rice. Mean ABTS activity of raw polished rice (0.8-1.9 mg TE/g) was the least followed by parboiled (1.2- 2.3 mg TE/g) and raw rice (1.3-2.1 mg TE/g). Mean DPPH scavenging and FRAP activities followed the same pattern with raw rice having the highest (4.5-6.2 mg AE/100g; 4.6- 14.4 mg AE/100g) followed by parboiled (4.4-5.1 mg AE/100g); 5.0-15.2 mg AE/100g) and the least in raw polished (4.0-4.6 mg AE/100g; 5.1-18.5 mg AE/100g) respectively. Phenolic compounds and antioxidant potential increased in the order of raw polished, parboiled, and raw rice flour in both cooked and uncooked rice. Rice grains with red coloured bran produced higher antioxidant activity compared to varieties with white bran. However, cooking reduced the antioxidant potentials in all differently processed varieties.
Keywords: Total phenol contents, Antioxidant capacities, Traditional rice, Parboiling, Milling, Polishing